Construction of CRISPR/Cas9_gRNA-OsCKX2 module cassette and its introduction into rice cv. Mentik Wangi mediated by Agrobacterium tumefaciens - MARINA RUZYATI; ATMITRI SISHARMINI; ANIVERSARI APRIANA; TRI JOKO SANTOSO; EDI PURWANTO; SAMANHUDI SAMANHUDI; AHMAD YUNUS (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ruzyati M, Sisharmini A, Apriana A, Santoso TJ, Purwanto E, Samanhudi, Yunus A. 2022. Construction of CRISPR/Cas9_gRNA-OsCKX2 module cassette and its introduction into rice cv. Mentik Wangi mediated by Agrobacterium tumefaciens. Biodiversitas 23: 2679-2689. Mentik Wangi is an aromatic superior rice variety from the tropical japonica group with high posture and low productivity. The tall plant posture causes Mentik Wangi rice to be prone to lodging, resulting in yield loss. Therefore, improvement of plant height and productivity of Mentik Wangi is still required. The sd-1 (OsGA20ox-2) and CKX2 genes are responsible for the semi-dwarf character and high productivity. The study aimed to construct a CRISPR/Cas9 cassette module carrying a gRNA of OsCKX2 gene and introduce this construct to Mentik Wangi rice mediated by an Agrobacterium tumefaciens vector strain LBA4404. The introduction of the CRISPR/Cas9_gRNA-GA20ox-2 cassette plasmid that was constructed in previous research into Mentik Wangi rice was also carried out. The results showed that the CRISPR/Cas9_gRNA-CKX2 cassette module had been successfully constructed using the Golden gate cloning method. The introduction of the CRISPR/Cas9_gRNA-CKX2 and CRISPR/Cas9_gRNA-GA20ox-2 cassette modules into Mentik Wangi rice resulted in 30 putative transformant lines that passed the hygromycin selection. PCR analysis showed that from the 30 transformant lines, 15 lines were positive for the hygromycin resistance gene. Further analysis is necessary to be conducted to identify the occurrence of mutagenesis in the OsCKX2 and GA20ox-2 target genes.